2020
DOI: 10.1186/s13048-020-0617-y
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of the combination chemotherapy of bevacizumab and gemcitabine in women with platinum-resistant recurrent epithelial ovarian, primary peritoneal, or fallopian tube cancer

Abstract: Introduction: Bevacizumab and gemcitabine are key drugs for treating recurrent epithelial ovarian cancer. However, information about the combination of bevacizumab and gemcitabine is insufficient. We conducted a phase II study to assess the feasibility, clinical activity, and toxicity of this combination chemotherapy. Methods: This study included women with platinum-resistant recurrent epithelial ovarian, primary peritoneal, or fallopian tube cancer who received one to three regimens of platinum-based chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Non-platinum-based agents or regimens are preferred (ie, docetaxel, oral etoposide, gemcitabine, weekly paclitaxel with or without pazopanib, liposomal doxorubicin with or without bevacizumab, weekly paclitaxel/bevacizumab) sequential therapy is usually performed with a single agent. 6,11,[19][20][21][22] Although notable progress has been made in the treatment of ovarian cancer, the prognosis of patients with the resistant or refractory disease remains poor. 4,23 Beyond chemotherapy, molecular targeted therapy plays an important role in the treatment of platinumresistant or platinum-refractory ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-platinum-based agents or regimens are preferred (ie, docetaxel, oral etoposide, gemcitabine, weekly paclitaxel with or without pazopanib, liposomal doxorubicin with or without bevacizumab, weekly paclitaxel/bevacizumab) sequential therapy is usually performed with a single agent. 6,11,[19][20][21][22] Although notable progress has been made in the treatment of ovarian cancer, the prognosis of patients with the resistant or refractory disease remains poor. 4,23 Beyond chemotherapy, molecular targeted therapy plays an important role in the treatment of platinumresistant or platinum-refractory ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…28 Bevacizumab combined with chemotherapy shown improved activity in platinum-resistant ovarian cancer. 6,11,12,[29][30][31][32] In AURELIA, the PFS of chemotherapy plus bevacizumab in patients with platinum-resistant disease is 6.7 months. However, the prolongation of OS in the bevacizumab group did not reach a significant level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of subanalyses suggested that only multidrug therapy with bevacizumab and paclitaxel improved both PFS and OS 13) . Nagao et al reported that when Ben-Gem therapy was administered to PSR patients, the median PFS and OS were 5.1 months and 21.3 months, respectively, and that Ben-Gem therapy was effective and safe 12) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that monotherapy with gemcitabine is effective for PRR disease 9,10) . However, there are only a limited number of reports on multidrug therapy with gemcitabine and bevacizumab (Bev-Gem therapy) 11,12) . Thus, we performed a retrospective study to evaluate the efficacy and safety of Bev-Gem therapy in PROC patients.…”
Section: Introductionmentioning
confidence: 99%